ANALISIS PERENCANAAN PEMBIAYAAN PENDIDIKAN ISLAM UNTUK MENINGKATKAN AKUNTABILITAS DI MTSN 10 TASIKMALAYA - Salma Raudya Rachma; Mulyawan Safwandy Nugraha (Hijri, 2025)
Education financing planning is a strategic aspect in madrasah management that plays an important role in ensuring accountability in financial management. This study aims to analyze the planning of education financing in MTsN 10 Tasikmalaya, identify the suitability of fund allocation with the needs of madrasas, and examine the accountability mechanisms applied. This study uses a qualitative approach with a descriptive method. Data was obtained through interviews with deputy heads of madrasas, treasurers, and related parties, and through the distribution of questionnaires to educators and education staff, and supported by documentation data in the form of RKAM and financial statements. The results of the study show that financing planning at MTsN 10 Tasikmalaya has been carried out in an accountable manner with an average of 93% in the very good category. Thus, financing planning at MTsN 10 Tasikmalaya is not only administrative, but also strategic in supporting the achievement of Islamic education goals.